191k views
3 votes
Example #5If K is the midpoint of CT, CK = 3x + 23,and KT = 5x + 7, then find x and CT.

Example #5If K is the midpoint of CT, CK = 3x + 23,and KT = 5x + 7, then find x and-example-1
User Kisp
by
4.8k points

1 Answer

1 vote

Since K is the midpoint of CT, it means that CK is equal to KT,


CK=KT

Then, replace with the corresponding expressions,


3x+23=5x+7

solve for x,


\begin{gathered} 3x-5x=7-23 \\ -2x=-16 \\ x=(-16)/(-2) \\ x=8 \end{gathered}

finally, find CT as the addition between CK and KT


\begin{gathered} CT=CK+KT \\ CT=(3x+23)+(5x+7) \\ x=8 \\ CT=3(8)+23+5(8)+7 \\ CT=24+23+40+7 \\ CT=94 \end{gathered}

Answer:


\begin{gathered} 1.\text{ }x=8 \\ 2.\text{ }CT=94 \end{gathered}

User Wal
by
4.7k points